ANALISIS PERAN AKTOR DALAM KOLABORASI PENYEDIAAN PERMUKIMAN LAYAK HUNI DI KOTA SURABAYA (STUDI KASUS PADA PROGRAM DANDAN OMAH) - Aldiansyah, Sulthan Zamrisyaf; Ma'ruf, Muhammad Farid (Publika, 2024)
In 2022, the Surabaya City Government launched the Dandan Omah program which is a continuation of the modified uninhabitable housing social rehabilitation program with a new concept. In its implementation, the Surabaya City Government collaborated with external parties, namely the Surabaya City Baznas, the Manarul Ilmi Foundation and KTPR. The purpose of this study is to identify the roles of actors involved in the collaboration in providing habitable housing in the city of Surabaya. This research is a type of qualitative research with a case study approach with content analysis techniques. The analysis was carried out by compiling a content analysis matrix to obtain positive and negative sentiments from each substance obtained from sources and from other supporting data. Data were collected through interview instruments, observation and documentation. The focus of the research is the role of actors consisting of 5 dimensions, namely: 1) policy creator; 2) coordinator; 3) facilitator; 4) implementor; 5) accelerator. The research findings show that the role of policy creator is carried out by the Surabaya City DPRKPP by developing a funding scheme outside the APBD through collaboration. The role of the Coordinator is carried out by the Surabaya City DPRKPP by providing written or unwritten information to other actors. The role of Facilitator is carried out by DPRKPP Surabaya City, Baznas Surabaya City, YMI ITS. The role of implementor is carried out by DPRKPP Surabaya City, Baznas Surabaya City, YMI ITS and KTPR by implementing the program according to mutual agreement. The role of Accelerator is carried out by DPRKPP Surabaya City through the promotion of the Dandan Omah logo on certain souvenirs. Research recommendations for collaborative actors of the Dandan Omah program to create an MoU if there is none and recommend publishing an MoU if there is one as a form of transparency to the public regarding the program run by the government.